2012
DOI: 10.1007/s00217-012-1743-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ca2+ and cellular structure on apple firmness and acoustic emission

Abstract: This study presents the influence of calcium lactate treatment (0-6 %) and cellular composition on two mechanical attributes: firmness and total acoustic emission (AE) events registered in the puncture test of apple tissue. The experiment was performed on five apple cultivars stored for nine months in a normal or controlled atmosphere. The microstructure was characterized quantitatively on control samples by confocal scanning laser microscope followed by image analysis. The mean area and perimeter of detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…The amplitude of the brittle sound at any time is the function of the volume of the sound generated by a single cell, and the cell wall crack volume (Dacremont, ); it is proportional to the load at the time of energy release, and therefore it may be expected that cell walls resistance to compression has an impact on acoustic measurements due to the greater amount of energy released in the process (Cybulska et al ., ). One factor strongly affecting the acoustic performance of brittle/crunchy products is their microstructure (Luyten & Van Vliet, 2006).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The amplitude of the brittle sound at any time is the function of the volume of the sound generated by a single cell, and the cell wall crack volume (Dacremont, ); it is proportional to the load at the time of energy release, and therefore it may be expected that cell walls resistance to compression has an impact on acoustic measurements due to the greater amount of energy released in the process (Cybulska et al ., ). One factor strongly affecting the acoustic performance of brittle/crunchy products is their microstructure (Luyten & Van Vliet, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Sounds generated during eating are important in crispy foodstuffs texture. The sound emitted by fresh fruit is a result of the rapid release of turgor pressure inside cells, and a sound wave is produced (Cybulska, Pieczywek, & Zdunek, ). Studies have shown that the combination of the acoustic analysis with mechanical testing and sensory evaluation ensures precise evaluation of the texture of dried apples (Marzec & Zadrożna, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pectinolytic enzymes cause structural changes of pectins, which affect cell walls and overall tissue firmness during maturation and storage (Cybulska et al 2010). The enzymes are widely used in the food industry as clarification agents for fruit juices, coffee and tea fermentations (Cybulska et al 2012). In addition, pectinolytic enzymes are involved in maintaining a balanced ecosystem, decomposing organic material from plants (Jayani et al 2005;AlimardaniTheuil et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to iron and calcium addition, magnesium caused a decrease of viscosity of MPS with increasing concentration. Changes in viscosity of MPS in calcium hydroxide solutions are associated with the cross-linking ability of polysaccharides, especially low-methylated pectin chains with calcium cations (Cybulska et al, 2012;Fang et al, 2008;Fraeye et al, 2010;Kastner et al, 2012;Ralet et al, 2003;Ventura et al, 2013;Videcoq et al, 2011;Yang et al, 2013;Yapo & Koffi, 2013). A significant increase of viscosity in the case of the addition of iron lactate may be explained as an ability of divalent iron ions to interact with polysaccharides resulting in the forming of an intermolecular network similar to the structure of Ca 2+ -low-methylated pectin.…”
Section: Viscositymentioning
confidence: 87%
“…To ensure edibility as well, the delivery system might be made of cell walls from fruit and the desired thickening could be gathered from pectin gelling ability. Most of the previous studies on pectin extracted from fruit or vegetable cell walls have concerned the ability of interaction of low methoxyl pectin chains with calcium cations (Cybulska, Pieczywek, & Zdunek, 2012;Fang et al, 2008;Fraeye et al, 2010;Kastner, Einhorn-Stoll, & Senge, 2012;Ralet, Crépeau, Buchholt, & Thibault, 2003;Ventura, Jammal, & Bianco-Peled, 2013;Videcoq, Garnier, Robert, & Bonnin, 2011;Yang, Zhang, Hong, Gu, & Fang, 2013;Yapo & Koffi, 2013). However, the review of the literature has revealed that there is only very little information on the interaction of pectin with other divalent metal cations, such as magnesium and iron.…”
Section: Introductionmentioning
confidence: 95%